Pemakaian Kawat Gigi Perspektif Hukum Islam: Studi Takhrij dan Syarah Hadis - Dzu Hulwin (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about the use of braces. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the use of braces in the history of Bukhari no. 4886. The results and discussion of this study indicate that the quality of hadith is shahih li dzaatihi that meets the qualifications of maqbul ma'mul bih for Islamic observation. This study concludes that the hadith narrated by Bukhari no. 4886 is relevant to be used as a guide, direction and development of the field of wearing braces.